Pemberdayaan Kader dan Pendampingan ASI Eksklusif Bagi Ibu Hamil di Desa Tanjung Anom, Kecamatan Pancur Batu, Kabupaten Deli Serdang - Citra Dewi Fitri; Nafi’atul Latifah; Asmima Yanti (STIKES Columbia Asia Medan, 2024)
Mother's milk (ASI) is the ideal food for babies. Preparation for exclusive breastfeeding should start during pregnancy. Successful exclusive breastfeeding requires a lot of support from the husband and family. Health cadres are the spearhead of providing health information in villages so it is necessary to empower health cadres in socializing exclusive breastfeeding to pregnant women. The aim of the activity is to empower health cadres regarding the importance of exclusive breastfeeding so that they can provide exclusive breastfeeding assistance for pregnant women. The activity method is to empower health cadres about exclusive breastfeeding. Before the activity, a pre-test and post-test are carried out as an evaluation. The tools and materials used are LCD, screen, leaflets, questionnaires. The sample was 15 health cadres. The results of the research, before empowering health cadres, were 8 health cadres who had sufficient knowledge about exclusive breastfeeding (53%) and 2 health cadres who had good knowledge about exclusive breastfeeding (13.3%). After empowering health cadres, there was an increase in health cadres' knowledge, namely 13 health cadres had good knowledge about exclusive breastfeeding (86.6%) and the remaining 2 health cadres had sufficient knowledge (13.3%). At the mentoring stage, 15 health cadres succeeded in assisting 15 pregnant women who were willing to prepare themselves during pregnancy to provide exclusive breast milk to their babies after birth. The conclusion is that there is an increase in the knowledge of health cadres after empowering health cadres so that pregnant women receive assistance in preparing for exclusive breastfeeding.